Analysis of Bank Holding Company Towards State-Owned Banks in Compliance with Single Presence Policy (The Indonesian Journal of Business Administration, 2012)
In order to establish a solid and stabile banking system, improve affectivity in monitoring role and preparation before the implementation of Basel III regulation, Bank Indonesia implemented policy to regulate ownership of banks which operate in Indonesia. The policy stated that one single that one single entity is restricted to solely holds majority share of more than one bank. This regulation also applies to four state-owned banks (BNI, Bank Mandiri, BRI, and BTN) which majority shareholders for those banks is the government of Indonesia. On February 2011, ministry of BUMN decided to operate a virtual holding in order to comply with PBI No. 8/16/PBI/2006. This study focus on the form of the holding company, scrutinizing the impact of current operating holding company, towards the functioning of its subsidiaries, the four state-owned banks, and towards the implementation of minimum capital adequacy ratio in accordance to Basel III. With the purpose to identify the impact of virtual holding existences, the valuation performed prior to and after the virtual holding company operates, resulting from discounted cash flow to equity method Vbefore for BNI; Bank Mandiri; BRI and BTN is 79 trillion rupiah; 143 trillion rupiah; 285 trillion rupiah and 7.420 trillion rupiah and Vafterfor BNI; Bank Mandiri; BRI and BTN is 92 trillion rupiah; 163 trillion rupiah; 288 trillion rupiah; and 7.286 trillion rupiah. The result of the valuation demonstrates that thre is insignificant increase of value upon each of four banks. Whereas to observe the capital adequacy, projected CAR analysis for 8 years was performed towards four state-owned banks. The projection resulting two of four banks’ CAR will be far bellow minimum capital adequacy requirement as regulated by Basel III. With CAR level in 2019 of 19.64% for BNI, 7.57% for Bank Mandiri, 10,05% for BRI, and 13,26% for BTN. Based on the calculation, the role of virtual holding company remains unsupportive upon performance of capital adequacy in accordance to Basel III for four state-owned banks. Therefore, the form of virtual holding company should be replaced by a fully functioned holding company. Within the implementation of fully function holding company formation, government through ministry of state owned companies ought to prepare one entity as a holding company for the four state-owned banks, appoint which choosen state-owned bank to take the role as holding company, perform share-swarp, complete the firm formation procedure as holding company, and form a organization structure. Keywords: single presence policy, bank holding company, bank valuation, Basel III.